PENGARUH KOMPENSASI TERHADAP KINERJA GURU HONORER PENDIDIKAN AGAMA ISLAM DI SD NEGERI 016 SAKO KECAMATAN PANGEAN - Fauzun Aisyah; Sarmidin Sarmidin; Andrizal Andrizal (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Problems in this study The effect of compensation on the performance of Islamic Religious Education teachers and the factors that influence it in SDO 016 Sako District Pengean District and the purpose of this study is to determine the effect of compensation onthe performance of Islamic Religious Education teachers and the factors that influence it in SD Negeri 016 Sako Pengean District As subjects in this study were 2 PAI teachers while as an object was the effect of compensation on the performance of PAI teachers in SDO 016 Sako District Pengean Based on the results of data collection by means of observation, questionnaires, interviews and documentation.Analysis of the data using the Spearman rho statistical product moment formula test can be concluded that: The effect of compensation on the performance of Honorary Teachers of Islamic Education in SDO 016 Sako, Pangean District is 40.96% while the rest 59.04% can be influenced by factors other, the better the compensation given to honorary teachers, thenautomatically the performance of honorary teachers of Islamic religious education will also be better too.The factors that influence the performance of Honorary Teachers of Islamic Education in State Elementary School 016 Sako Pangean are as follows: Knowledge, skills, abilities, selfconfidence,motivation, commitment owned by Honorary Teachers of Islamic Religious Education The existence of giving encouragement, enthusiasm, direction, and support given the principal to the Honorary Teacher of Islamic Education. Lack of quality support andenthusiasm provided by colleagues in the profession, namely honorary teachers. The work system, the work facilities provided by the leadership of the school principal are the same responsibilities as PNS / ASN teachers